A Review of Spinal and Peripheral Neuromodulation and Neuroinflammation: Lessons Learned Thus Far and Future Prospects of Biotype Development. Issue 3 (12th October 2018) - Chakravarthy, Krishnan V.; Xing, Fang; Bruno, Kelly; Kent, Alexander R.; Raza, Adil; Hurlemann, Rene; Kinfe, Thomas M.
Abstract : Background: There is increasing literature evidence both clinically and experimentally on the existence of potent, adaptive interactions between the central and peripheral aspects of the neuroimmune system in the genesis and maintenance of chronic neuropathic extremity pain and nociceptive back pain. The neuroinflammatory pathways are modulated by the interaction of pro‐ and anti‐inflammatory cytokines and chemokines, which are released by peripheral immune system‐derived cell species (macrophages and leukocytes). This review examines the possible impact of spinal and peripheral neurostimulation on the inflammatory response in the context of acute and chronic pain pathologies of different origin. Study Design: A narrative review of preclinical and clinical studies addressed to the spinal cord and peripheral nerve stimulation and neuroinflammation. Methods: Available literature was reviewed on neurostimulation technologies and both acute and chronic low‐grade inflammation to identify primary outcome measures and to provide an overview of postulated mechanisms of action of neurostimulation on host inflammatory responses. Data sources included relevant literature identified through searches of PubMed, MEDLINE/OVID, SCOPUS, and manual searches of the bibliographies of known primary and review articles. Results: A comprehensive review of the literature indicates an alternate or synergistic mechanism of action of neurostimulation, beyond modulating somatosensory pain pathways, in modifying inflammatory response associated with chronic pain, by promoting a systemic anti‐inflammatory state with upregulation of anti‐inflammatory mediators. Conclusions: These preliminary findings may have important implications on the potential applications of neurostimulation as an anti‐inflammatory therapy and the role of molecular profiling as a preimplant screening modality and post‐implant outcome validation. Thus, future targeted clinical and experimental research is highly warranted in this particular novel field of neuromodulation.